A Review on Concept of Trividha Pariksha and its Importance - Amrutha, D C; Rathee, Deepak; Desai, Ananta S (International Research Journal of Ayurveda & Yoga, 2022)
To find out the root cause of a disease in Ayurveda, there are certain examinations that are compulsory to be conducted. In today’s clinical practice diagnosis of a disease is very crucial. Proper examination of patient and disease is the path to successful clinical practice. This helps to build up a doctor-patient relationship. Trividha pariksha viz. Aptopadesha, Pratyaksha, Anumana and Darshana, Sparshana, Prashna are the two different aspects of Trividha pariksha which helps to achieve the above-mentioned goals. There are various methods of examination explained in our treatises but Trividha pariksha holds the basis of all among them. They play a key role in the diagnosis of disease. Therefore, an effort is made through this article to review the importance of Trividha pariksha and its relevance in today’s clinical practice. Materials And Methods: Various literature, published articles, and other documents were studied thoroughly and a conclusion was made. Discussion: Though we have various examination and diagnostic methodologies but Trividha pariksha are base for all of them and still hold a great importance in diagnosis and management of the disease. Result: Prashana pariksha, history taking is pearl of Ayurveda and Vaidya should be expert in this. A disease can be known only through proper combination of all these examination methods only